Managerial skills of women entrepreneurs in Dobrudgea's rural area - Elena Sima (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Women have become more important in the global market, not just as employees, but also as consumers, entrepreneurs, managers and investors. This paper aims to capture the managerial skills of women entrepreneurs in Dobrudgea's rural area and the difficulties that women entrepreneurs are facing, the gender differences and gender diversity in business, as well as their impact on the economy. By approaching this theme, we intend to highlight the problems faced by women both in terms of concepts and education by analyzing the employment rate by age, status and education level. Although women are still a minority in entrepreneurship and entrepreneurial skills and women workforce in rural areas are underused, in recent years there has been a considerable increase worldwide in the number of women who start and run their own business. Moreover, it is a general characteristic of Eastern European countries, which have the lowest levels of women's participation in entrepreneurial activities.
Keywords: 330; women entrepreneurs; managerial skills; rural area; Dobrudgea